Methodological And Applicative Ijtihad Yusuf Al-Qardhawi In Solving Contemporary Issues - Asrizal Saiin (TASAMUH: Jurnal Studi Islam, 2021)
Over time, with the issue of closing the door of ijtihad, it does not become a barrier for contemporary Islamic figures to come up with new ideas as alternative solutions to problems, as well as Yusuf al-Qardhawi. The purpose and objective of this research is to see the method and application of al-Qardhawi's ijtihad in solving contemporary issues. This research is included in the qualitative research method. The source of data used in this study is a secondary data source, because it will examine the literature or literature. Processing and data analysis in this study, namely editing, classifying, verifying, analyzing, and concluding. The results obtained in this study are that there are three kinds of methodologies and alternatives in ijtihad offered by al-Qardhawi, namely ijtihad Intiqa'i (selective ijtihad), ijtihad insya'i (creative ijtihad), and integration ijtihad between Intiqa'i and insya'i.